A multi-criteria framework for office tenants' preferences at office buildings - Adnan, Yasmin Mohd; Daud, Md Nasir; Mohamed Razali, Muhammad Najib (International Journal of Strategic Property Management, 2015)
In order to mitigate the anticipated oversupply of office space, it is necessary to gauge the preference of office occupiers, namely tenants of purpose built office buildings, since these tenants form the indicator of demand for space. In this study, a multi-criteria decision making method (MCDM) – the Analytic Hierarchy Process (AHP) procedure was employed to analyse the relative importance of the main factors chosen by the main sectors of tenants at top grade office buildings in Kuala Lumpur city centre. This study had identified the elicitation of experts’ opinion and tenants’ selection comprises twenty-six important factors for office occupation in Kuala Lumpur city centre, grouped under four main categories: Location, Lease, Building and Financial/Cost. This study then employed AHP to assess the relative importance placed on each category, revealing the varying patterns of preferences when tested on tenants from three main business sectors occupying top grade office buildings. The findings showed that, between the three sectors (Finance/Banking, ICT & Media and Oil & Gas), differences in preference were only slight for most factors but were significant for a few. The findings from this study are insightful in informing decisions on future office provision, particularly in the context of working towards satisfying office tenants’ requirements.First Publish Online: 9 Oct 2015